Os outros somos nós: cordel e elaboração de livro paradidático de química para pessoas com deficiência visual - Santos, Michele Batista dos (2021)
The increase in enrollment of people with disabilities in regular public schools has increased the demand for research in the area. In this context, this research used the three axes proposed by Gabriel Kaplún to elaborate a informational books for students with visual impairments. The conceptual, pedagogical and communicational axis. Finally, it should be noted that the objectives of this research were carried out. The general objective was to understand the teaching of chemistry for students with visual impairments and from that point on, a informational books was developed that brought something new and differentiated to the area, a sensory and first-person narrative that addresses radioactivity, content little explored by research with educational materials, and so it was possible to explore the potential of this material. Also carrying out the specific objectives, as an inclusive and easily informational book was created, which also leverages resources to help improve language and orality, using cordel literature in the pedagogical itinerary, and this same itinerary proposes methodologies for applying informational books. from the theoretical assumptions of the area. Thus, like referrals for new research, the actual application of this material remains to broaden the objectives and contribute even more to inclusive education.